2020
DOI: 10.1021/acscatal.0c02657
|View full text |Cite
|
Sign up to set email alerts
|

Ene/Diene Copolymerization Catalyzed by Cationic Sc and Gd d0 Metal Complexes: Speciation, Ion Pairing, and Selectivity from a Computational Perspective

Abstract: metallocene • d 0 metal complexes • butadiene • polymerization • speciation • ion pairing • reactivity • DFT ABSTRACT A computational mechanistic study of the butadiene homopolymerization reaction performed with scandium and gadolinium catalysts [(2-Me-Ind)2(N(TMS)2)]M (M = Sc, Gd) in presence of [Ph3C][B(C6F5)4] or [PhNMe2H][B(C6F5)4] and Al2Et6 has been performed at the DFT level. The speciation of mono-and poly-metallic complexes involving alkylaluminum and the cationizing agent has been achieved. Their dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
(146 reference statements)
0
11
0
Order By: Relevance
“…However, the experimental estimates are not based on the T dependence of K d so we cannot attach too much significance to these discrepancies, except to state that we did not consider more than one conformer when calculating thermodynamic properties. 26…”
Section: Resultsmentioning
confidence: 99%
“…However, the experimental estimates are not based on the T dependence of K d so we cannot attach too much significance to these discrepancies, except to state that we did not consider more than one conformer when calculating thermodynamic properties. 26…”
Section: Resultsmentioning
confidence: 99%
“…We first examine the structure of active species and the possibility of a Gd‐alkyl species by DFT calculations, and next investigate the mechanism of ethylene polymerization reaction. Recent experimental and computational studies showed that various ion pairs can be generated in an activation process for polymerization reaction with boron‐C 6 F 5 compounds such as B(C 6 F 5 ) 3 and [Ph 3 C][B(C 6 F 5 ) 4 ] and aluminum alkyl species through Al/B transmetalation [18,19] . Perrin et al., however, adopted B(C 6 F 5 ) 4 − in their DFT calculations for polymerization reactions, to avoid considering various possibilities, although they found stable ion pairs with Et 2 B(C 6 F 5 ) 2 − or AlEt 4 − [19] .…”
Section: Resultsmentioning
confidence: 99%
“…The copolymerization of olefins, including ethylene, with conjugated dienes has been one illustration of this challenging objective. This has been achieved by identifying the adequate catalysts [3][4][5][6][7][8][9][10][11][12] that produced copolymers combining the advantageous properties of olefins-and conjugated dienesbased homopolymers. 13 Among the catalysts reported, {(Me2Si(C13H8)2)Nd(-BH4)[(-BH4)Li(THF)]}2 (1) / BOMAG (BOMAG = n-butyl-n-octylmagnesium) (Scheme 1) enabled the copolymerization of ethylene with butadiene and gave access to a new class of rubber called ethylene butadiene rubber (EBR).…”
Section: Introductionmentioning
confidence: 99%
“…The copolymerization of olefins, including ethylene, with conjugated dienes has been one illustration of this challenging objective. This has been achieved by identifying adequate catalysts 3–12 that produced copolymers combining the advantageous properties of olefin- and conjugated diene-based homopolymers. 13…”
Section: Introductionmentioning
confidence: 99%